Les principes de la restauration d’instruments scientifiques : le cas du cercle méridien Gautier de l’observatoire de Rio de Janeiro - Marcus Granato; Françoise Le Guet Tully (In Situ)
This article opens with some general remarks on the principles of restoring scientific instruments and on the presentation of the restoration policies of the Brazilian museum of astronomy (MAST). It then gives a brief history of the astronomical observatory at Rio de Janeiro and presents in particular the history of one of its major instruments, a meridian circle built for the observatory at the end of the 19th century by the celebrated French maker of scientific instruments Paul Gautier. It describes how this meridian circle, dismantled during the 1960s and given to the museum of astronomy (MAST) has recently been the object of an important restoration programme. This operation led to the inauguration, in 2006, of a new space in the museum devoted to this instrument.